PC sound card based instrumentation and control - Gunawan, Teddy Surya; Khalifa, Othman Omran (2010)
The availability of inexpensive PC sound cards that can simultaneously play and record stereo digital audio files permits a single PC or laptop or netbook to function as both a signal generator and as a dual-channel recording digital oscilloscope. This paper presents how sound card with Matlab Data Acquisition Toolbox can be utilized for instrumentation and control. The buffer hardware circuit or signal conditioning circuit is developed and implemented to enable sound card to be functioned like oscilloscope. Preliminary results showed that sound card with the developed software has a good potential for instrumentation and control.